Investigation of constraints to health and production of cattle in North-East Bangladesh (Bangladesh Veterinarian, 2022)
The study was designed to investigate the constraints to health and productivity of dairy farms and their possible remedies in Sadar Upazila (sub-district) of Sylhet, Sreemangal Upazila at Moulavi Bazar, Chatak and South Sunamgonj Upazila at Sunamgonj districts. Ninety dairy farms including marginal and small (2-10 cows), medium (11-25 cows) and large (>25 cows) of urban, suburban and rural areas were randomly selected for multistage sampling. Farmers were interviewed using pre-tested questionnaire. The major constraints were high price of concentrate, poor knowledge of feeding, scarcity of forage, weak recording system, cost of high yielding well-adapted milking cows, prolonged postpartum anoestrus, repeat breeding, incorrect timing of AI, mastitis, low pregnancy rate, lack of milk co-operative, weak milk marketing and high veterinary cost. To overcome the current situation government should give incentives on cattle feed and credit facility with soft interest to the farmers; DLS and other organizations should arrange effective training on dairy farm management.The Bangladesh Veterinarian (2020) 37(1 - 2): 1-13